Paradoxical embolism caused by ovarian vein thrombosis extending to inferior vena cava in a female with uterine myoma. Issue 6 (December 2018) - Nakamura, Shun; Tokunaga, Takeshi; Yamaguchi, Aya; Kono, Toshikazu; Kasano, Kensuke; Yoshiwara, Hirotaka; Hattori, Eijiro; Niwa, Akihiro; Hirao, Kenzo
Abstract: Deep vein thrombosis occasionally causes paradoxical embolism in patients with a patent foramen ovale (PFO). We report the case of a 42-year-old female who was hospitalized for stroke. Detailed investigations revealed the existence of a PFO, pulmonary embolism, and ovarian vein thrombosis extending to inferior vena cava. She had a uterine myoma to be operated on but no other thrombophilic disorders. Anticoagulation therapy with direct oral anticoagulant successfully reduced the thrombus and prevented the recurrence of paradoxical embolism. <Learning objective: Ovarian vein thrombosis (OVT) is often associated with malignancy, pelvic surgery, or pregnancy. This case shows uterine myoma as a possible cause of OVT and demonstrates the efficacy of direct oral anticoagulant for the treatment of OVT and inferior vena cava thrombosis.>